Pengaruh Lingkungan Kerja Dan Kualitas Layanan Pasien Terhadap Kinerja Karyawan Pada Rumah Sakit Umum Afdila Cilacap - Kartika, Kartika; Syahrinullah, Syahrinullah (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
The purpose of this study is to identify and evaluate factors that are likely to have a significant impact on employee performance at Afdila Cilacap General Hospital, as well as the simultaneous effect of work environment and patient service quality on employee performance. This study used a quantitative approach, with a sample size of fifty people and a population of one hundred employees. The data analysis techniques used are multiple linear regression, validity test, reliability test, T test, and F test. The results of this study show that the variables that have a significant effect simultaneously on the employee performance variable of Afdila Cilacap General Hospital are the work environment and the quality of patient service. The performance variable of Afdila Cilacap General Hospital employees is not significantly influenced by the work environment or the quality of patient service. The work environment at Afdila Cilacap General Hospital is the factor that most affects employee performance